Pengaruh Pajak Daerah, Retribusi Daerah, dan Produk Domestik Regional Bruto Terhadap Kapasitas Fiskal Kota Pontianak - Widyaningsih, Atria Tiffany (Fakultas Ekonomi dan Bisnis, UNTAN, 2018)
Based on regression equation result, local tax has negative influence to fiscal capacity so that if local tax increase IDR1 that impact decrease in fiscal cmcity equal to -27,449. It is stated that the rise and fall of the value of local tax realization has an effect on the income and allocation of expenditure of a region that support public expenditure infrastructure in fulfilling the economic requirement of society. The regional ratio has a negative influence on fiscal capacity so that if the regional retribution increases IDR1 resulted in a decrease in fiscal capacity of-28.216. This suggests that the rise and fall of the value of realization of regional levies affects the income of a region and the allocations of expenditure that support public expenditure infrastructure in meeting the economic needs of the community. PDRB has a positive influence on fiscal capacity so that if the PDRB increases IDR1 resulted in a decrease in fiscal capacity of 211,076,629.